Interdiffusivity matrices and atomic mobilities in fcc Co–Ni–Si and Cu–Co–Ni–Si alloys: Experiment and modeling. (March 2023) - Liu, Huixin; Wen, Shiyi; Liu, Yuling; Du, Changfa; Min, Qianhui; Zheng, Zhoushun; Du, Yong
Abstract: Accurate diffusion kinetics information of fcc Co–Ni–Si alloys is essential for developing high-performance Cu–Co–Ni–Si alloys. Eight diffusion couples at the Co–Ni side are assembled to determine the Co- and Ni-basis diffusivities of fcc Co–Ni–Si alloys at 1273 or 1373 K. The diffusivity matrices at the intersection compositions of diffusion paths are determined by the Matano-Kirkaldy method. In addition, the diffusivity matrices along the whole composition profiles and the atomic mobilities of fcc Co–Ni–Si alloys are evaluated by the numerical inverse approach. The reliability of the obtained atomic mobilities is verified by comparing the predicted diffusion phenomena with the experimental ones. Strong cross phenomenon effects among the components are manifested by large negative cross diffusivities, the development of zero flux planes and uphill diffusion phenomena. The uphill diffusion in the fcc Co–Ni–Si system is due to the cross phenomenon between diffusion components. The location of the zero flux plane of a component is usually the intersection between the diffusion path and the iso-activity line for that component through a terminal alloy. Combining the mobility descriptions of the fcc Co–Ni–Si system with the other three sub-ternary systems in the literature, the atomic mobilities in fcc Cu–Co–Ni–Si alloys are constructed. The model-predicted composition profiles of Cu–Co–Ni–Si alloys show a good agreement with the experimental ones, validating the accuracy of the obtained atomic mobilities. Highlights: Eight diffusion couples close to Co–Ni side are assembled to determine the Co- and Ni-basis diffusivities of fcc Co–Ni–Si alloys at 1273 or 1373 K. The diffusivity matrices along the whole composition profiles and the atomic mobilities of fcc Co–Ni–Si alloys are evaluated by the numerical inverse approach incorporated in CALTPP. Strong diffusional interactions among the components are manifested by large negative cross-diffusion coefficients, the development of zero-flux planes and uphill diffusion behaviors. The location of zero-flux plane of a component is usually the intersection between the diffusion path and the iso-activity line for that component through a terminal alloy.